Patterns of Trust and Collaboration among Nonprofit Organizations and Health Funds: A Case Study - Vered Reiter; Shay S. Tzafrir; Nathaniel Laor (Journal of Public and Nonprofit Affairs, 2018)
The importance of collaboration between organizations, especially in the modern world, has been discussed extensively by researchers from different fields. Yet, the importance of the context, trust dynamics, and the employment social environment, such as the interplay among these factors, i.e., trust, individual behavior, and political behavior, has been less studied. This study evaluates the role of trust in and between organizations on successful collaboration processes. Using qualitative methodology, we interviewed 11 senior directors who were involved in a specific case-study of collaboration among four major organizations as well as direct observation, documentation, and archive records. Our findings emphasize the importance of analyzing multilevel trust, interpolitics, and intrapolitics, even when success is at stake. We suggest that managers have to account for emotional involvement at the individual level, even when successful organizational-level collaboration occurs. Overall, we found that there are two aspects of trust in a collaboration process between organizations: system’s aspect and personal aspect. Each aspect is influenced by various factors, mainly different goals and interest and lack of procedures or regulations (from the system’s aspect) and feelings of vagueness in goals and managerial procedures as well as feelings of exploitation (from the personal aspect). In addition, we found that past acquaintances, mutual experience, and shared visions raise the level of trust, which in turn affects the reciprocal relations and therefore the collaboration process resulting in higher social effectiveness for social services.